UJI AKTIVITAS ANTIDIARE INFUSA BIJI PAPAYA (Carica papaya) PADA MENCIT JANTAN (Mus musculus) TERINDUKSI Oleum ricini - Rizka Laila Fitriyah; Ni Wayan Putri Utami; Husnul Qarina; Rizky Ayu Apriliana; Zulhi Shepiana Pasti; Nurjihad Nurjihad; Siti Rahmatul Aini (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2023)
Diarrhea is a major health problem in Indonesia, and West Nusa Tenggara (NTB) is the province with the highest prevalence of diarrheal disease in Indonesia. Papaya (Carica papaya) is empirically used for the management of diarrhea. This study aims to determine the effective empirical dose of infused papaya seeds which were tested in vivo in castor oil-induced mice. This study used 5 treatment groups, namely papaya seeds infusion 1,3 g/kg body weight dan 2,6 g/kg body weight, normal control, negative control, and positive control capsule x containing guava leaf, turmeric rhizome, mojokeling fruit, and pomegranate peel extract. All groups of mice except the normal control group were induced orally with castor oil. LSIR, ALSG, and DI were measured and analyzed using the One Way Anova and post-hoc LSD tests with SPSS v.25 software. Infusion of papaya seeds (Carica papaya) has been shown to have anti-diarrheal efficacy at an empirical dose of 1.3 g/kg body weight in terms of the Average Loose Stool Grade parameter and diarrhea index comparable to capsule X.